Implicit, Explicit, and Structural Barriers and Facilitators for Information and Communication Technology Access in Older Adults - Gomez-Hernandez, Miguel; Adrian, Stine Willum; Ferre, Xavier; Villalba-Mora, Elena (Frontiers in Psychology, 2022)
Older adults’ usage of information and communication technology (ICT) is challenged or facilitated by perception of usefulness, technology design, gender, social class, and other unspoken and political elements. However, studies on the use of ICT by older adults have traditionally focused on explicit interactions (e.g., usability). The article then analyzes how symbolic, institutional, and material elements enable or hinder older adults from using ICT. Our ethnographic methodology includes several techniques with Spanish older adults: 15 semi-structured interviews, participant observation in nine ICT classes, online participant observation on WhatsApp and Jitsi for 3 months, and nine phone interviews due to COVID-19. The qualitative data were analyzed through Situational Analysis. We find that the elements hindering or facilitating ICT practice are implicit-symbolic (children’s surveillance, paternalism, fear, optimism, low self-esteem, and contradictory speech-act), explicit-material (affordances, physical limitations, and motivations), and structural-political (management, the pandemic, teaching, and media skepticism). Furthermore, unprivileged identities hampered the ICT practices: female gender, blue-collar jobs, illiteracy, and elementary education. However, being motivated to use ICT prevailed over having unprivileged identities. The study concludes that society and researchers should perceive older adults as operative with technologies and examine beyond explicit elements. We urge exploration of how older adults’ social identities and how situatedness affects ICT practice. Concerning explicit elements, Spanish authorities should improve and adapt ICT facilities at public senior centers and older adults’ homes, and ICT courses should foster tablet and smartphone training over computers.